Lipasin, a biomarker of diabetic retinopathy. (May 2016) - Fang, Chen; Huang, Yun; Guo, Heming; Gao, Yan; Ji, Xiaoyan; Hu, Ji
Highlights: We reported for the first time that lipasin level is found to be elevated in type 2 diabetic patients with diabetic retinopathy. Our report indicated lipasin is not only a lipid regulator but also may be a new biomarker for DR. Abstract: The present study recruited 74 participants with type 2 diabetes, among which 23 had retinopathy. Those with retinopathy had a longer duration of diabetes and higher levels of lipasin compared with those without retinopathy. Logistic regression revealed that lipasin was independently and significantly associated with retinopathy even after adjustments for confounders.